Evaluation of the Immunological Markers IL-10 and IL-12 in Patients with Systemic Lupus Erythematous - AbdAlameer, Ali Mohammed (Journal of natural sciences, life and applied sciences, 2025)
Objectives: The current study focuses on evaluating the serum levels of both cytokinin IL-10 and IL-12 in patients with systemic lupus erythematosus and investigating their association with disease activity. Methods:.A case–control study was conducted on Forty-six patients infected with lupus erythematous (41 females and 5 males), and 30 healthy volunteers (22 females and 8 males), with age ranged from 13 to 45 years were collected from Department of Chronic Diseases in Marjan Medical City in Babylon Governorate, Iraq. The hospital’s consultant doctors diagnosed patients with systemic lupus erythematosus in accordance with the applicable clinical standards. The levels of cytokines IL-10 and IL-12 were measured using ELISA technology, and disease activity was assessed with the SLEDAI score, which incorporates clinical and laboratory features to quantify disease severity. Results: The concentrations of IL-10 and IL-12 in the serums of erythematosus patients compared to healthy people (p < 0.05) with a positive correlation between IL-10 and IL-12 levels in the patient group The study revealed significantly higher serum concentrations of IL-10 and IL-12 in patients with SLE compared to healthy controls (p < 0.05). Moreover, both cytokines demonstrated a positive correlation with each other and showed significant positive associations with the SLEDAI score, highlighting their potential role in reflecting disease activity. Conclusions: High serum levels of IL-10 and IL-12 indicate a possible synergistic role that may contribute to the various effects of causing SLE. Full knowledge of understanding the interaction and the role that these two cytokines play may lead to better insights into the mechanism of the disease and the development of new treatments to prevent damage to SLE, prevent organ damage in SLE. Conclusions: Elevated serum levels of IL-10 and IL-12, together with their correlation with the SLEDAI index, suggest a synergistic role in disease activity and progression. A better understanding of their interactions may provide valuable insights into SLE pathogenesis and support the development of new strategies to prevent organ damage.